A Profile of Street Noise in Dumaguete City, Philippines, 2008 - Bandal, Hope Maxino (Silliman Journal, 2022)
This paper contains the results of a research done on street noise in Dumaguete City, using 90 different observation points or locations. It includes data on sound pressure level (SPL), traffic density (number of vehicles per minute), and construction layout such as width of the street, make and construction type of buildings, and the presence of trees and open spaces beside the streets. The method involves measurement of the sound pressure level and traffic density using three runs in each location and solving for the correlation coefficient r between traffic density and sound pressure level. The results indicate that there is a high correlation (r = 0.7342) and thus, a marked relationship, between sound pressure level and traffic density. The results of the study also indicate that 20% (18 locations) of the observation points had SPL values of 75 dB and above. Furthermore, analysis of the data indicates that the SPL depends not only on the traffic density but also on the layout of buildings and roads and the presence of trees and open areas nearby. Also, a frequency analysis of the noise was done using a sound sensor in combination with a computer interface. This showed the traffic noise with the highest sound pressure level to be in the 200 Hz-400 Hz frequency range, generally.